Analysis of the intricate relationship between chronic inflammation and cancer - Chai, E.; Siveen, K.; Shanmugam, M.; Arfuso, Frank; Sethi, G. (Portland Press Ltd, 2015)
Deregulated inflammatory response plays a pivotal role in the initiation, development and progression of tumours. Potential molecular mechanism(s) that drive the establishment of an inflammatory-tumour microenvironment is not entirely understood owing to the complex cross-talk between proinflammatory and tumorigenic mediators such as cytokines, chemokines, oncogenes, enzymes, transcription factors and immune cells. These molecular mediators are critical linchpins between inflammation and cancer, and their activation and/or deactivation are influenced by both extrinsic (i.e. environmental and lifestyle) and intrinsic (i.e. hereditary) factors. At present, the research pertaining to inflammation-associated cancers is accumulating at an exponential rate. Interest stems from hope that new therapeutic strategies against molecular mediators can be identified to assist in cancer treatment and patient management. The present review outlines the various molecular and cellular inflammatory mediators responsible for tumour initiation, progression and development, and discusses the critical role of chronic inflammation in tumorigenesis.